The socio-environmental history of the Peloponnese during the Holocene: Towards an integrated understanding of the past. (15th March 2016) - Weiberg, Erika; Unkel, Ingmar; Kouli, Katerina; Holmgren, Karin; Avramidis, Pavlos; Bonnier, Anton; Dibble, Flint; Finné, Martin; Izdebski, Adam; Katrantsiotis, Christos; Stocker, Sharon R.; Andwinge, Maria; et al.
Abstract: Published archaeological, palaeoenvironmental, and palaeoclimatic data from the Peloponnese in Greece are compiled, discussed and evaluated in order to analyse the interactions between humans and the environment over the last 9000 years. Our study indicates that the number of human settlements found scattered over the peninsula have quadrupled from the prehistoric to historical periods and that this evolution occurred over periods of climate change and seismo–tectonic activity. We show that societal development occurs both during periods of harsh as well as favourable climatic conditions. At some times, some settlements develop while others decline. Well-known climate events such as the 4.2 ka and 3.2 ka events are recognizable in some of the palaeoclimatic records and a regional decline in the number and sizes of settlements occurs roughly at the same time, but their precise chronological fit with the archaeological record remains uncertain. Local socio-political processes were probably always the key drivers behind the diverse strategies that human societies took in times of changing climate. The study thus reveals considerable chronological parallels between societal development and palaeoenvironmental records, but also demonstrates the ambiguities in these correspondences and, in doing so, highlights some of the challenges that will face future interdisciplinary projects. We suggest that there can be no general association made between societal expansion phases and periods of advantageous climate. We also propose that the relevance of climatic and environmental regionality, as well as any potential impacts of seismo-tectonics on societal development, need to be part of the interpretative frameworks. Graphical abstract: Highlights: Explorative investigation of human-environment dynamics in the Peloponnese from the Neolithic to the Medieval period. Review of archaeological, palaeoenvironmental, and palaeoclimatic datasets. Identification and initial interpretation of chronological linkages between societal development and palaeoenvironmental records. Demonstration of the ambiguities in many linkages and illustration of remaining challenges for future interdisciplinary projects.